International perspectives on higher education : challenging values and practice - Kerry, Trevor (Continuum, 2012)
Trevor Kerry draws together contributions from leading academics in the field based in Europe, Canada and Australia to examine key themes in higher education, including:? academic freedom? leadership and management? the nature of learning and teaching? ethical behaviour? curriculum innovation? attitudes to globalization and internationalizationThe contributors explore what might constitute effective higher education provision, drawing on innovative practice from around the world and encouraging higher education practitioners to become more analytical and critical about their institutions ...